2012
DOI: 10.1159/000339680
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Pollutants and Acute Case-Fatality of Cerebro-Cardiovascular Events: Takashima Stroke and AMI Registry, Japan (1988–2004)

Abstract: Background: Apart from the conventional risk factors, cerebro-cardiovascular disease (CVD) are also reported to be associated with air pollution, thus lowering the level of exposure might contribute in prevention activities to reduce the associated adverse outcomes. Though few studies conducted in Japan have reported on the CVD mortality but none have explored the effect of air pollutant exposure on the acute case-fatality of CVD. We investigated the effects of air pollution exposure on acute case-fatality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…Several studies reported associations between short-term exposure to particle matter, including several size fractions, or gases and any stroke mortality. Only a few studies further characterized stroke into ischemic and hemorrhagic stroke mortality 24, 3335, 38 . Short-term exposure to particulate matter and gases were associated with both ischemic stroke and hemorrhagic stroke.…”
Section: Short-term Air Pollution Exposurementioning
confidence: 99%
“…Several studies reported associations between short-term exposure to particle matter, including several size fractions, or gases and any stroke mortality. Only a few studies further characterized stroke into ischemic and hemorrhagic stroke mortality 24, 3335, 38 . Short-term exposure to particulate matter and gases were associated with both ischemic stroke and hemorrhagic stroke.…”
Section: Short-term Air Pollution Exposurementioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] Our results were most robust for NO x , which remained associated with cardiovascular event risk even after accounting for unmeasured confounders and even showed some association after adjusting for other pollutants. However, we note that while performing multipollutant analyses is common practice within environmental epidemiology, the results should be interpreted cautiously, as the interpretation requires holding all other pollutants fixed, which may not be realistic for teasing out the 'independent' pollutant effect.…”
Section: Discussionmentioning
confidence: 56%
“…1 Increased risk of non-fatal cardiovascular or cerebrovascular events is seen with exposure to particulate matter with aerodynamic diameter <10 μm (PM 10 ) and <2.5 μm (PM 2.5 ), nitrogen oxide (NO x ), ozone, carbon monoxide (CO) and sulfur dioxide (SO 2 ). [2][3][4][5][6][7][8][9][10][11] Some subpopulations may be particularly sensitive to air pollution exposure, such as the elderly, diabetics and persons with obesity or existing cardiac disease. 12 13 Given the physiological changes in pregnancy, including increased oxygen requirements and cardiac output, elevation in plasma volume, changes in vascular resistance and blood pressure, hypercoagulability and higher risk of acute myocardial infarcts, 14 15 we hypothesise that air pollution may be associated with increased risk for maternal cardiovascular events during or immediately after labour and delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have evaluated risk factors for SAH, and the risk factors of age, female sex, hypertension, and tobacco use are supported by strong evidence [4,5]. In addition, genetic predisposition and alcohol and drug abuse are the most commonly discussed risk factors [6,7,8,9,10,11,12,13,14,15,16,17,18]. However, whether or not seasonal or meteorological factors influence SAH is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%